Prevention of tuberculosis transmission in the household: An investigation of knowledge, attitudes, and practices in West Halmahera Regency, Indonesia - Rosmila Tuharea; Hamidah Rahman; Elok Dian Kusumawati Gather; Dwi Rossa Anggraini Sagala (Advances in Medicine, Psychology, and Public Health)
Introduction: Emphasizing the significance of tuberculosis (TB) in the family environment is crucial due to the high rate of transmission among members of the household. This phenomenon has been proven by molecular epidemiological studies using fingerprint D.N.A. analysis to describe the easy transmission incidents in the family environment. Therefore, this study aimed to determine TB patients' knowledge, attitudes, and practices (KAP) in preventing transmission among family members in West Halmahera Regency, North Maluku Province, Indonesia. Methods: This study was conducted using a cross-sectional design, including 150 TB patients as respondents selected through a sampling method. A structured questionnaire was used as an interview guide for face-to-face data collection. The analysis was conducted from January to June 2023, and the data obtained were analyzed using descriptive statistics with a frequency distribution table and supplemented by narrative. Results: The results showed that 91 respondents (60.7%) had a good level of knowledge, 76 (50.7%) had favorable attitudes, and 81 (54.0%) had good practices in prevention of TB transmission. Although KAP was in a good category, there were still 43 respondents (28.7%) with TB patients in other family members. Conclusions: The data obtained showed a possibility of TB transmission to other family members in the household due to a lack of KAP in prevention. Monitoring and patient access to pulmonary TB drugs was also found to be suboptimal. Consequently, proactive efforts are essential to enhance prevention in families to eliminate TB patients in line with the objectives stated in the national strategy for controlling TB in Indonesia.